Insecticidal Activity of Ethanolic Extract of Mentha piperata Leaves against Cotton Aphid Aphis gossypii Glover on Okra Crop (Abelmoschus esculentus) - Kavita Vidyarthi, Sunita Sharma and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: Different concentrations of ethanolic extract of Mentha piperata leaves were tested against the adult apterous females and third instar nymphs of aphid Aphis gossypii infesting okra crop. This aphid is a major limiting factor for the profitable cultivation of okra. The aphicidal activity of Mentha piperata extract was examined on Aphis gossypii with the counted number of third instar nymphs and adult viviparous females. The 2% concentration of the extract has resulted in 100% mortality of nymphs and adults in 72hrs. and 96hrs. time period respectively. The lower concentration of 1.5% also caused 100% mortality but required more time of 96hrs. At 2% concentration the LT50 value for nymphs and adults were 13.37 and 26.66hrs. The extract of M. piperata can be used as a potent insecticide for the control of cotton aphid A. gossypii infesting okra plants. Key words: Cotton aphid, Aphis gossypii, Insecticidal activity, Mentha piperata, okra crop Pest and Parasite Research laboratory, Post Graduate Dept. of Zoology, Bareilly College, Bareilly- 243005 (U.P.) Please Cite This Article As: Sunita Sharma and Kavita Vidyarthi. 2010. Insecticidal Activity of Ethanolic Extract of Mentha piperata Leaves against Cotton Aphid Aphis gossypii Glover on Okra Crop (Abelmoschus esculentus). J. Exp. Sci. 1(5):11-13.